(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
This article provides information about the establishment of the Khiva State Museum-Reserve “Ichan Qal’a” and its collections of applied arts, Khorezm masters of applied arts, unique exhibits in the museum.